Taḥlīlu Al ‘Anāṣiri Al Jāwhārīyati Fī Filmi “Ḍyb” Lī Naji Ābu Nowar (Dirāstun Taḥlīliyyatun Fī ‘Ilmi Al Ādabi) - Indriyati, Reny; Buska, Wahyudi (Al-Uslub: Journal of Arabic Linguistic and Literature, 2025)
Abstract: The purpose of this study was to determine the intrinsic elements (theme, plot, characterizations, setting, language style) in the film "Theeb" by Naji Abu Nowar, and to determine the moral message in the film "Theeb" by Naji Abu Nowar. This research uses qualitative research. The data source for this research is the Jordanian Arabic film “Theeb”, and from several related or relevant books, journals, and theses. The object of this research is the intrinsic elements contained in the film Theeb. Using the documentation method with a descriptive approach which was analyzed using inductive data analysis. The results of the analysis of Theeb film's research, there are two themes in this film, namely major and minor themes, the conflict of changes in manual transportation using camels and horses with Hijaz rail transportation and the introduction of Bedouin cultural customs. There are three plots in Theeb's film, namely the beginning of the conflict, the culmination of the conflict, and the settlement. The plot in Theeb's film uses a forward plot. There are six dominant characters in Theeb film, namely Theeb, Husein, Sheikh, Marji, Edward, and Hasan. This film has five place settings and three time settings, namely the Theeb family settlement, Roman Well, Mountain or Cliff, Train, and Station. The setting of this film is Morning, Afternoon, and Night. This film has two language styles, namely rhetorical and figurative. This film has two moral messages, namely the moral message of human relations with themselves and human relations with other humans. From the results of the analysis in Theeb film, it can be concluded that this film has two themes, three plots, six characters, five place settings, three time settings, two language styles and two moral messages